2011
DOI: 10.1021/ja202243j
|View full text |Cite
|
Sign up to set email alerts
|

Nanospheres of a New Intermetallic FeSn5 Phase: Synthesis, Magnetic Properties and Anode Performance in Li-ion Batteries

Abstract: We synthesized monodisperse nanospheres of an intermetallic FeSn(5) phase via a nanocrystal-conversion protocol using preformed Sn nanospheres as templates. This tetragonal phase in P4/mcc space group, along with the defect structure Fe(0.74)Sn(5) of our nanospheres, has been resolved by synchrotron X-ray diffraction and Rietveld refinement. Importantly, FeSn(5), which is not yet established in the Fe-Sn phase diagram, exhibits a quasi-one dimensional crystal structure along the c-axis, thus leading to interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 23 publications
4
84
0
Order By: Relevance
“…In 2005, Sony corporation applied the amorphous Sn–Co–C composites as negative electrodes for its new‐type lithium‐ion batteries, named “Nexelion.”17, 18 This breakthrough had ignited great passion from people in researching of Sn‐based alloys. To date, a series of Sn‐based intermetallics alloyed with inactive metals have been investigated as potential anodes for LIBs and/or SIBs, including Fe–Sn,73, 76, 77, 78 Co–Sn,79, 80, 81, 82, 83, 84, 85 Cu–Sn,86, 87, 88, 89 Ni–Sn,23, 90, 91, 92 Mn–Sn,93, 94, 95 La–Sn,96, 97 Ce–Sn,98 Cr–Sn,99, 100 etc.…”
Section: Alloying Modification Of Sn‐based Anode Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2005, Sony corporation applied the amorphous Sn–Co–C composites as negative electrodes for its new‐type lithium‐ion batteries, named “Nexelion.”17, 18 This breakthrough had ignited great passion from people in researching of Sn‐based alloys. To date, a series of Sn‐based intermetallics alloyed with inactive metals have been investigated as potential anodes for LIBs and/or SIBs, including Fe–Sn,73, 76, 77, 78 Co–Sn,79, 80, 81, 82, 83, 84, 85 Cu–Sn,86, 87, 88, 89 Ni–Sn,23, 90, 91, 92 Mn–Sn,93, 94, 95 La–Sn,96, 97 Ce–Sn,98 Cr–Sn,99, 100 etc.…”
Section: Alloying Modification Of Sn‐based Anode Materialsmentioning
confidence: 99%
“…Therefore, it is important to find Sn‐based intermetallic compounds with high Sn content. Han's group78, 84, 102 discovered MSn 5 (M = Fe, Co, and Fe 0.5 Co 0.5 ) series intermetallic phases with stoichiometric structural vacancies. Fe 0.74 Sn 5 , Co 0.83 Sn 5 , and Fe 0.35 Co 0.35 Sn 5 exhibit the highest theoretical capacities (>917 mA h g −1 ) among the Sn‐based binary and ternary alloys (M are inactive).…”
Section: Alloying Modification Of Sn‐based Anode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, intermetallic compounds, such as Sn-Ni alloys, Sn-Co alloys, Sn-Cu alloys, and Sn-Fe alloys, are employed to solve the volume expansion problem during discharge/charge (Zhang et al, 2008). In the development of high-performance, lithium ion battery, anode structures (Paul et al, 2005;Richter and Eberhard, 2005), FeSn 2 has been shown to have the best composition among the Fe-Sn intermetallic compounds (Naille et al, 2007;Chamas et al, 2011;Wang et al, 2011). The cycling performance of the FeSn 2 intermetallic compound is constant over 50 cycles at a specific capacity higher than 400 mAhg -1 ; the specific capacity is higher for a FeSn 2 /graphene composite electrode, exhibiting a higher capacity than the conventional carbonaceous anode (372 mAhg -1 ) (Mao and Dahn, 1999;Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The tin (Sn)-based LIBs anodes, cycling between Sn and Li4.4Sn, exhibit an attractive theoretical specific capacity of 994 mA h g −1 [9]. Moreover, Sn meets the major requirements for replacing the current graphite LIBs anodes owing to its high abundance and non-toxicity [10,11].…”
Section: Introductionmentioning
confidence: 99%